A checklist of the Kharkiv region Charales (Charophyta) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
First checklist of the Kharkiv region Charales (Charophyta) is compiled on the basis of previously reported and original data. Overall it includes 15 species (37.5% of the total number of Ukrainian charalean algae) belonging to the genera Chara L. (8), Nitella C. Agardh (4), Nitellopsis Hy (1) and Tolypella (A. Braun) A. Braun (2). The most frequent species are C. globularis Tuill., C. vulgaris L., Nitella mucronata (A. Braun) Miq. in H.C. Hall and Nitellopsis obtusa (Desv. in Loisel.) J. Groves. The rest are rare (6) and endangered (5 species). Among the rare taxa, Tolypella glomerata (Desv. in Loisel.) Leonh. is new to the algal flora of Ukraine as well as T. prolifera (Ziz ex A. Braun) Leonh., Chara intermedia A. Braun and C. tomentosa L. are new to the Leftbank Forest-Steppe of Ukraine. The checklist contains information on localities, some ecological characteristics, general distribution and sozological status of all species. Some new localities of rare species proposed for conservation have been presented.
Keywords: Chara, Nitella, Nitellopsis, Tolypella, rare species, Ukraine.